Graham Allison et le paradigme bureaucratique : vingt-cinq ans plus tard est-il encore utile ? - Michaud, Nelson (Études internationales, 1996)
Twenty-five years ago, Graham T. Allison brought to the political scientists community a new tool to help us to understand questions in the domain of Foreign Policy : the Bureaucratic Politics Model. Since then, his Essence of Decision has been one of the most read books in Universities and one of the texts most referred to in scholar works. However, it is of interest to analyze if, beyond the framework's reputation and despite the numerous criticisms addressed to it, the bureaucratic politics is still useful for someone who wishes to do analysis based on Us elements. How bureaucratic politics can still help us to better understand the decision-making processes ? Are there avenues, questions or problems that still can be better explained by referring to this scheme ? The answer we offer to these questions refers to the model's components, to an update of the evaluation several scholars made of it, and, finally, to a dynamic orientation that puts forward the paradigmatic dimension of the theory and an application to a specific question.